Ergonomic Assesment Keluhan Muskuloskeletal dan Sikap Tubuh Pekerja Ikan Asar di Desa Hative Kecil - Robert Hutagalung; V. O. Lawalata; D. Tumanan; Imelda K.E. Savitri (Industrial Engineering Study Program, Pattimura University, 2012)
Especially to man power task, musculoskeletal complaints related to work have caused by unfitting posturs of workers exposured during their daily tasks implemetation. Accordingly, research was conducted to assess the risk and determine the location of musculoskeletal complaints that pottentially occur in the body of ikan asar processing workers in Hative Kecil. The results, based on the comparation of RULA and NBM data analysis, show that detail investigations and changes hove to be done immediately to minimize the impacts since the complaints are taken place at level of 2 and 4. Neck, shoulders, back, arms (upper and low), wrists, elbows, waist, thighs, knees, calves, ankles and legs are founded as complaints locations.